Evaluation of the immunogenicity and diagnostic interference caused by M. tuberculosis SO2 vaccination against tuberculosis in goats. (December 2015) - Bezos, Javier; Casal, Carmen; Puentes, Eugenia; Díez-Guerrier, Alberto; Romero, Beatriz; Aguiló, Nacho; de Juan, Lucía; Martín, Carlos; Domínguez, Lucas
Abstract: The immunogenicity and diagnostic interference caused by M. tuberculosis SO2, a prototype vaccine first time tested in goats was evaluated. Tuberculosis-free goats were distributed in four groups: [1], non-vaccinated; [2], subcutaneously (SC) BCG vaccinated; [3], intranasally (IN) SO2 vaccinated and [4], SC SO2 vaccinated. Intradermal tuberculin and IFN-γ tests using PPDs and alternative antigenic cocktails containing mainly ESAT-6 and CFP-10 (E/C) were applied at different times post-vaccination. Results showed a significant (p < 0.05) increase in the number of reactors detected using both PPD-based intradermal and IFN-γ tests at different times in all the vaccinated groups. No intradermal reactivity was detected in the vaccinated goats using a cocktail containing E/C, Rv3615c and Rv3020c. A higher overall reactivity was observed in the group [4] in comparison with the other vaccinated groups. Results showed that antigens used to differentiate BCG vaccinated animals could be potentially used to differentiate SO2 vaccinated ones. Highlights: Mycobacterium tuberculosis SO2 vaccine is first time tested in goats. SO2 and BCG vaccines interfere with the diagnosis of tuberculosis using PPDs. Subcutaneous injection of SO2 vaccine shows a higher immunogenicity than the intranasal route. Cocktails containing ESAT-6, CFP-10, Rv3615c and Rv3020c show potential usefulness to differentiate SO2 vaccinated animals.